PHYSICAL ACTIVITY PROGRAMMES WITHOUT PRESCRIPTION AND FOLLOW-UP DONT CAUSE EFFECTS IN ANTHROPOMETRICAL, BIOCHEMICAL AND PULMONARY VARIABLES OF AGED WOMEN WITH OVERWEIGHT AND OBESITY (Fiep Bulletin - online, 2011)
This study evaluated the effect of a physical activity community programme in aged women anthropometrical, biochemical and pulmonary variables. Took part in the study 28 aged women with overweight and obesity, being 14 previously sedentary ones (SG, 68,7+5,5years) and 14 previously active in aerobical activities, carried out in community centers without individualized exercises prescription (FAG, 68,1+4,5 years). It was done a nutritional intervention with both groups for three months. The FAG did light aerobical exercises routinely twice a week, during forty five minutes a day and continued with these exercises during the intervention. The two groups were evaluated according to the anthropometry, spirometry, dynamic cirtometry and fat and glycolic profile before and after three months follow-up. In the initial evaluation, FAG didn't show itself better than the SG in any variable, indicating inefficiency of the exercise that was been done. After the three months of exercises and nutritional follow-up the FAG group presented Just a tendency for the HDL-c levels increase, triglycerides reduction, VLDL-c reduction, waist/hip relation, as well as improvement of the forced expiratory volume in the first second in percentage (FEV1%), of the expiratory flow peak (EFP) and of the expiratory reserve volume do volume (ERV). These data conduct us to the following assumptions: 1- The exercise practice without individualized professional follow-up don't promote improvement of the anthropometrical and biochemical chronicle diseases risk factors; 2- Intervention with nutritional orientation tends just to an improvement of these risk factors; 3- intervention also with exercises prescription seems to be necessary to intensify the nutritional intervention effects. Therefore, we concluded that the women who practiced exercises in community centers without an individualized prescription don't benefit themselves with chronicle degenerative diseases risk factors reduction.
Keywords: elderly; nutritional intervention; physical activity